Studies on Solanum torvum Swartz rootstock on cultivated eggplant under excess moisture stress - Kumar, Sanjeev; Patel, NB; Saravaiya, SN (Bangladesh Journal of Botany, 2019)
A field experiment on grafting two cultivars of brinjal, namely Surati Ravaiya Pink and Surati Ravaiya Purple onto the rootstock of Solanum torvum Swartz was conducted to elucidate the influence on plant survival and other horticultural parameters under excess moisture stress. The results revealed 24.59 and 17.18% higher plant survival in grafts of Surati Ravaiya Pink and Surati Ravaiya Purple over their respective counter parts. Plant growth indicators like plant height and stem diameter showed significant increase in grafts over normal plants. Grafted plants were quite early in flowering taking 38.60 and 34.53 days in Surati Ravaiya Pink and Surati Ravaiya Purple, respectively which corresponded significantly for earliness in picking by more than 5 days. Grafting also regulated heterostyly polymorphism positively and significantly in both the cultivars resulting in higher fruit set in grafted plants. Higher number of fruits per plant and enhanced cropping period were also important yield contributing traits achieved through grafting. The grafted plants showed tolerance to shoot and fruit borer exhibiting 22.79 and 17.86% infestation in Surati Ravaiya Pink and Surati Ravaiya Purple, respectively. Economic parameters analysis revealed higher net returns in grafted plants compared to non-grafted ones.